Matnyak S.V. Proof of the correctness of the Piemann's hypothesis. - Матняк, С.В. (Problems of Tribology, 2014)
The paper provides proof of the Rimann's conjecture. The results of the works of A. M. Odlyzko and H. te Riile "Disproof of the Conjecture", which gives a disproof of the hypothesis Mertens, using to prove the Riemann's hypothesis. This paper introduces new finite series of exponential function, which is determined by the number of even. The number of multiple natural numbers compared with the amount of the functional progression and faund is their numerical value. The paper introduces new concepts in analytic number thery as "natural numbers thah overlap". Also, a theorem proved, which gives a more accurate result for "notrivial zeros" than the Riemann's hypothesis.